Interactions of Elevated CO2 and Nitrogen Fertilization: Effects on Production of Bacillus thuringiensis Toxins in Transgenic Plants - Coviella, Carlos Eduardo (2000)
Fil: Coviella, Carlos Eduardo. Universidad Nacional de Luján. Laboratorio de Ecología; Argentina.